On the transposon origins of mammalian SCAND3 and KRBA2, two zinc-finger genes carrying an integrase/transposase domain - Llorens, Carlos (Landes Bioscience, 2012)
SCAND3 and KRBA2 are two mammalian proteins originally described as “cellular-integrases” due to sharing of a similar DDE-type integrase domain whose origin and relationship with other recombinases remain unclear. Here we perform phylogenetic analyses of 341 integrase/transposase sequences to reveal that the integrase domain of SCAND3 and KRBA2 derives from the same clade of GINGER2, a superfamily of cut-and-paste transposons widely distributed in insects and other protostomes, but seemingly absent or extinct in vertebrates. Finally, we integrate the results of phylogenetic analyses to the taxonomic distribution of SCAND3 and KRBA2 and their transposon relatives to discuss some of the processes that promoted the emergence of these two chimeric genes during mammalian evolution.